The Role of Health Promotion in Management Development. A Systematic Review of Training Concepts in an Organizational Context - Michael Hans Gino Kraft (Business Ethics and Leadership)
Economic success often depends on the health of managers and employees in the company. In this context, health promotion programs are becoming increasingly important to ensure the quality of work and for reducing absenteeism. Although academic interest in the study of individual health in organizations is growing, there is still a need for research to fully understand its potential in the area of management development as well. Under this premise, this article summarizes the arguments and counter-arguments within the scientific discussion on health-promoting aspects in the context of management development. The purpose of this work is to systematically deepen the understanding of corporate health promotion by reviewing the relevance of health-related aspects in management training concepts. Given this evidence, this work contains a systematic literature review about management training programs and empirical contributions. The review took place between November 2020 and February 2021 by using different scientometric databases such as Econbiz, Scopus and Web of Science. Among 56 identified publications, 20 studies address such management training concepts in the context of health issues. The paper provides initial evidence of differing understandings of health promotion in management development and identifies difficulties in implementing and prioritizing health promotion in training programs on the management level. Even though health-promoting topics are becoming increasingly important, self-leadership aspects still play a subordinate role in development programs. The study proved that despite the economic importance of the individual health of employees and managers, health promotion is still seen as a self-reflective task. Practitioners are therefore invited to test the potential of health-promoting elements in management training and to implement them in organizational reality.